2023
DOI: 10.1126/sciadv.adg2829
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of cFLIP restrains cell death during viral infection and tissue injury and favors tissue repair

Abstract: Cell death coordinates repair programs following pathogen attack and tissue injury. However, aberrant cell death can interfere with such programs and cause organ failure. Cellular FLICE-like inhibitory protein (cFLIP) is a crucial regulator of cell death and a substrate of Caspase-8. However, the physiological role of cFLIP cleavage by Caspase-8 remains elusive. Here, we found an essential role for cFLIP cleavage in restraining cell death in different pathophysiological scenarios. Mice expressing a cleavage-re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…While apoptosis is paramount for skin regeneration, it is clear that proper control of apoptotic cell death rates determines the healing kinetics. This is also exemplified in a mouse model in which the crucial cell death regulator cFLIP can no longer be cleaved by caspase-8, resulting in exaggerated cell death and a significant delay in skin regeneration [138]. Not only do extrinsic apoptotic pathways mediate skin regeneration, but the deregulation of intrinsic apoptotic signalling in HFSCs can accelerate cutaneous wound responses [139].…”
Section: The Impact Of Cell Death On Skin Regenerationmentioning
confidence: 99%
“…While apoptosis is paramount for skin regeneration, it is clear that proper control of apoptotic cell death rates determines the healing kinetics. This is also exemplified in a mouse model in which the crucial cell death regulator cFLIP can no longer be cleaved by caspase-8, resulting in exaggerated cell death and a significant delay in skin regeneration [138]. Not only do extrinsic apoptotic pathways mediate skin regeneration, but the deregulation of intrinsic apoptotic signalling in HFSCs can accelerate cutaneous wound responses [139].…”
Section: The Impact Of Cell Death On Skin Regenerationmentioning
confidence: 99%
“…Mice expressing CYLD D215A develop normally, suggesting that cleavage of CYLD at D215 is not essential to repress necroptosis [25]. cFLIP, another caspase-8 substrate that regulates necroptosis, did not undergo lethal necroptosis when its cleavage was genetically blocked in mice [25,26]. Furthermore, we and others have shown that rather than just inhibiting necroptosis, caspase-8-mediated RIPK1 cleavage is a mechanism to dissociate complex II/RIPoptosome to block apoptosis and autoinflammation [25,[27][28][29][30].…”
Section: Introductionmentioning
confidence: 94%
“…cFLIP ( CFLAR ) is a direct substrate and regulator of Caspase-8. It regulates levels of apoptosis by restraining the full activation of Caspase-8 [ 4 ]. Yet, the cFLIP/Caspase-8 heterodimer still bears sufficient activity to prevent another type of cell death called necroptosis [ 5 ].…”
Section: Introductionmentioning
confidence: 99%